2016
DOI: 10.2113/econgeo.111.6.1397
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal Alteration Revealed by Apatite Luminescence and Chemistry: A Potential Indicator Mineral for Exploring Covered Porphyry Copper Deposits

Abstract: Apatite is a common resistate mineral occurring in a range of host rocks and ore-related hydrothermal alteration assemblages. Apatite in several porphyry copper deposits in British Columbia has a unique set of physical and compositional characteristics that can be used to evaluate the chemical conditions of magmas that formed the causative intrusions or associated hydrothermal alteration. Apatite under visible light and SEM shows no notable variations between unaltered and altered varieties but cathodoluminesc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(81 citation statements)
references
References 50 publications
4
55
0
3
Order By: Relevance
“…Exploration for porphyry deposits whose outcrop is obscured by cover has encouraged the development of indicator mineral studies, in which dense and/or chemically stable minerals found in the erosional products of porphyry systems may be used to identify the presence of concealed hypogene mineralization (e.g., Averill 2011, Kelley et al 2011, Eppinger et al 2013. In British Columbia, this approach has been developed through study of trace element chemistry of specific rock-forming minerals, such as apatite (e.g., Bouzari et al 2016;Mao et al 2016), magnetite (e.g., Celis…”
Section: Introductionmentioning
confidence: 99%
“…Exploration for porphyry deposits whose outcrop is obscured by cover has encouraged the development of indicator mineral studies, in which dense and/or chemically stable minerals found in the erosional products of porphyry systems may be used to identify the presence of concealed hypogene mineralization (e.g., Averill 2011, Kelley et al 2011, Eppinger et al 2013. In British Columbia, this approach has been developed through study of trace element chemistry of specific rock-forming minerals, such as apatite (e.g., Bouzari et al 2016;Mao et al 2016), magnetite (e.g., Celis…”
Section: Introductionmentioning
confidence: 99%
“…We combined our Cl isotope data collected on multiple apatite crystals with information from two complementary analytical methods: transmission electron microscopy (TEM) and cathodoluminescence (CL) imaging, which we used to investigate microdomain textures and other internal features that may provide evidence for the preservation of primordial structures or their transformation at the micro-and nano-scales. Both methods have previously been shown to be useful in tracing products of the fluid-apatite reactions [69] and the hydrothermal alteration of apatite [70,71].…”
Section: Laboratory Methodsmentioning
confidence: 99%
“…Previous research on porphyry copper deposits containing apatite [70] showed that hydrothermal alteration can change the bright yellow luminescence of apatite to green colors via the mechanism of Mn 2+ removal (lower Mn/Fe ratio), and such an effect is coupled with the depletion of Cl, Si, and Na. Our apatite samples AL35-6 and AL15B have greenish luminescence colors and both are chlorine-poor (Table 1).…”
Section: Micron-scale Heterogeneity Of Isua Apatite Crystals and Its mentioning
confidence: 99%
“…Rukhlov et al (2016) also analysed apatite from a variety of porphyry systems and showed that alkalic porphyry systems could be discriminated from calc-alkalic systems, probably due to the more oxidized state and less evolved magmas associated with the former. Bouzari et al (2016) carried out a similar study and showed that apatite associated with different porphyry alteration styles could be discriminated by cathodoluminescence colour and certain chemical characteristics such as Mn/Fe ratio. Again, however, there was no explicit discrimination of porphyry-related apatite from other sources of the mineral.…”
Section: Apatitementioning
confidence: 99%
“…17). Similar vectoring potential is offered by apatite (Bouzari et al, 2016). Given the instability of magnetite in phyllic and intermediate argillic alteration, it is assumed that magnetite present in these domains is a partially overprinted relic from precursor potassic or propylitic assemblages.…”
Section: Hydrothermal Magnetitementioning
confidence: 99%